Brain metabolomics in rats after administration of ketamine. (23rd June 2015) - Wen, Congcong; Zhang, Meiling; Zhang, Yuan; Sun, Fa; Ma, Jianshe; Hu, Lufeng; Lin, Guanyang; Wang, Xianqin
Abstract: In this study, we developed a brain metabolomic method, based on gas chromatography–mass spectrometry (GC/MS), to evaluate the effect of ketamine on rats. Pattern recognition analysis, including both principal component analysis and partial least squares‐discriminate analysis revealed that ketamine induced metabolic perturbations. Compared with the control group, the levels of glycerol, uridine, cholesterol in rat brain of the ketamine group (50 mg/kg, 14 days) decreased, while the urea levels increased. Our results indicate that metabolomic methods based on GC/MS may be useful to elucidate ketamine abuse through the exploration of biomarkers. Copyright © 2015 John Wiley & Sons, Ltd.